2022
DOI: 10.1021/acs.jmedchem.2c01498
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Assessing Acceptable Intakes for Novel N-Nitrosamines Derived from Active Pharmaceutical Ingredients

Abstract: The detection of N-nitrosamines, derived from solvents and reagents and, on occasion, the active pharmaceutical ingredient (API) at higher than acceptable levels in drug products, has led regulators to request a detailed review for their presence in all medicinal products. In the absence of rodent carcinogenicity data for novel N-nitrosamines derived from aminecontaining APIs, a conservative class limit of 18 ng/day (based on the most carcinogenic N-nitrosamines) or the derivation of acceptable intakes (AIs) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 141 publications
(257 reference statements)
1
38
0
Order By: Relevance
“…As described in this Perspective, the Cohort of Concern as originally envisaged contained all N -nitroso compounds; however, even at the time it was noted that a substantial proportion of N -nitroso compounds were of lower potency than the TTC, and subsequent research has confirmed that the carcinogenic potencies of nitrosamines span no fewer than 4 orders of magnitude . Those N -nitroso compounds that do lead to potent carcinogenicity are those that can form a diazonium ion in close proximity to DNA and thus lead to its alkylation; their potency is related to the facility with which that diazonium can be formed. ,, As a result, the following observation can be made: not all N -nitroso compounds should be in the CoC, and indeed, not even all N -nitrosamines should be in the CoC considering that the presence of an α-hydrogen is critical for high carcinogenic potency.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…As described in this Perspective, the Cohort of Concern as originally envisaged contained all N -nitroso compounds; however, even at the time it was noted that a substantial proportion of N -nitroso compounds were of lower potency than the TTC, and subsequent research has confirmed that the carcinogenic potencies of nitrosamines span no fewer than 4 orders of magnitude . Those N -nitroso compounds that do lead to potent carcinogenicity are those that can form a diazonium ion in close proximity to DNA and thus lead to its alkylation; their potency is related to the facility with which that diazonium can be formed. ,, As a result, the following observation can be made: not all N -nitroso compounds should be in the CoC, and indeed, not even all N -nitrosamines should be in the CoC considering that the presence of an α-hydrogen is critical for high carcinogenic potency.…”
Section: Discussionmentioning
confidence: 98%
“…The Ames test is ultimately used as a proxy for potential carcinogenicity under ICH M7, and it is worth noting that the predictivity of this assay is significantly higher , for N -nitrosamines than it is for other genotoxic carcinogens. In addition to this work by Trejo-Martin et al, ongoing efforts from the FDA, the EMA MutaMind Project, and HESI GTTC seek to confirm the optimal conditions (OECD TG471 allows for a variety of approaches) for N -nitrosamine detection in the Ames test …”
Section: Implications For Toxicity Testingmentioning
confidence: 99%
See 3 more Smart Citations